Because you're mine - Kleypas, Lisa (Avon Books, 1997)
Young, high-spirited Lady Madeline Matthews is expected to wed an aging, lecherous lord. But she would rather shame herself in the eyes of society than sacrifice her freedom, and resolves to render herself unmarriageable by indulging in a torrid affair with Britain's most acclaimed actor and notorious womanizer, Logan Scott.